THE RELATIONSHIP BETWEEN THE LEVEL OF PUBLIC KNOWLEDGE ABOUT COVID-19 VACCINATION AND THE ANXIETY OF THE IMPACT OF THE COVID-19 VACCINE IN HAMLET II RT 009 RW 003 KALIBUAYA KARAWANG VILLAGE IN 2022 - Handayani, Sri; Meliyana, Ernuli; Meriyandah, Hilda (Rena Cipta Mandiri, 2023)
The COVID-19 pandemic is currently a serious world problem with the number of cases always increasing every day. Attacking everyone regardless of age or gender and has been categorized as a global pandemic. Until now, the COVID-19 vaccine has still received a lot of rejection from the public. Especially for people in villages where there is still a lot of information about the COVID-19 vaccine, so that people have more confidence in the issues circulating about the COVID-19 vaccine. This researcher aims to determine the relationship between the level of public knowledge about COVID-19 vaccination with anxiety about the impact of the COVID-19 vaccine in Dusun II RT 009 RW 003 Kalibuaya Karawang Village in 2022. The research methods used by this researcher are quantitative. With this type of Cross Sectional Analytical research, the sampling technique used in the study was a purposive sampling technique with a total sample of 96 respondents. Based on the results of research conducted by researchers in Dusun II RT 009 RW 003 Kalibuaya Karawang Village in 2022, the results of the Chi Square statistical test were obtained, namely obtained the Value of Asymp Significance (0.000) < the value of α (0.05), this shows that H0 was rejected. Thus, it can be concluded that there is a Relationship between the Level of Public Knowledge about Covid-19 Vaccination with anxiety about the Impact of the Covid-19 Vaccine in Hamlet II RT 009 RW 003 Kalibuaya Karawang Village in 2022.